Health care seeking behavior of pregnant women in Gusau Metropolis of Zamfara State, Northern Nigeria - Maiwada, Abdullahi Mohammed; A. Rahman, Nor Azlina; Abdul Rahman, Suzanah; Mamat, Nik Mazlan; A-Baba, Tukur (Federal University Gusau Nigeria, 2016)
Purpose: The objectives of the study were to determine the health care seeking behavior and the barriers to hospital delivery of pregnant women in Gusau metropolis of Zamfara State, Northwest Nigeria. Also the study was to identify those factors that prevent women from delivering at the hospital and access care. Methods: The study used both survey and qualitative technique. In the survey a descriptive cross sectional survey involving with patients based on a structured questionnaire format with answer sets was used to ask about (N=826) pregnant women attending antenatal care at some clinics in Gusau metropolis about how, why, where and when they seek care and how they perceive certain illness during pregnancy. While about 6 focus group discussions (FGDs) were conducted at the health facilities targeting the pregnant women in order to understand their illness behavior and perception to facility delivery. During the FGDs notes were taken and answers recorded using a tape recorder and video. Results: 87.9% of the respondents said they attend Antenatal care clinics (ANC) regularly and many of the respondents have some knowledge of complications during pregnancy, N=177 reported having headache, N=221 and N=227 reported having fever and swelling of legs respectively.87.1% of those attending ANC indicated that they will seek care at hospital or clinic. Though, responses in the FGDs, many of the respondents indicated that they seek care at health facility but will however not want to deliver at the hospital. Conclusion: There is a remarkable improvement in attendance of ANC by pregnant women but yet the hospital delivery is very low and not exciting as many women wished to deliver at home rather than in the hospital. Also many of the women’s perception about their health or illness during pregnancy are that they think it is normal to be sick and therefore not necessary to visit the clinic. There is still high preference for home delivery among the pregnant women in Zamfara State, with a consequent increased in maternal deaths unreported.